Augmenting ENT surgery outside the medical school curriculum: the role of a 1-day otolaryngology course. Issue 4 (10th April 2019) - Spiers, H; Enayati, H; Moussa, R; Zargaran, A; Thomas, A; Murtaza, A; Turki, M; Ofo, E
Abstract: Background: ENT is highly under-represented in the saturated UK medical school curriculum, comprising less than 1 per cent of the curriculum. A 1-day course was implemented in order to raise awareness of ENT among medical students, educate them in the specialty and teach a basic skill. Methods: The skills day comprised lectures by consultants followed by a consultant-led workshop teaching tracheostomy. Pre- and post-course questionnaires assessed perceptions of ENT, confidence performing tracheostomy and interest in ENT as a career. Results: Perceptions of ENT as a specialty were improved by up to 80 per cent ( p < 0.01). There was improved understanding of and confidence in performing tracheostomies. Interest in a career in ENT was increased by 77 per cent ( p < 0.01). Conclusion: A 1-day course run by a student body can be a powerful adjunct to the medical school curriculum, in terms of educating undergraduates in ENT and inspiring the pursuit of ENT as a career.